Improving Students’ Cognitive Ability through Flannel Board Media of Group B1 at TK Aisyiyah Padang Bintungan Dharmasraya - Sesmita, Desi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
Cognitive ability at Aisyiyah Kindergarten, Padang Bintungan is still low, this can be seen in counting pictures according to the symbols of numbers 1-20, showing number symbols based on pictures 1-20, Pairing symbols according to the number of pictures 1-20. The purpose of this study was to improve children's cognitive abilities through flannel board media. The type of this research is classroom action research. This research was conducted at TK Aisyiyah Padang Bintungan, Group B1 with 17 children. The data were obtained from observations, interviews, and documentation in the form of photos processed by the percentage technique. Classroom action research was conducted in two cycles. The results of the research in each cycle have shown an increase in children's cognitive abilities from cycle I which are generally still low. In Cycle I the increase in children's cognitive abilities was seen to be still low in accordance with the percentage of success rates and continued in cycle II the increase in children's cognitive abilities became more improved and showed positive results, it was seen that the achievement of the percentage of children's success increased. So that the average success rate of children exceeds the minimum completeness criteria (KKM) that have been set. Based on the results of the study, the average cognitive ability of children through flannel board media in the initial conditions was low which was 14.626%, and in the first cycle it increased to 74.5%, and in the second cycle it increased to 78.9%. This means that flannel board media is proven to increase the moral value of children in Aisyiyah Kindergarten, Padang Bintungan.